Handbook of higher education in Japan - Snowden, Paul (Japan Documents, 2021)
This Handbook tells the story in 25 chapters of how Japan's HE system has become what it is now, ending with a very tentative glimpse into the rest of the 21st century. A variety of themes are covered by scholars--both established, senior figures and younger researchers with their own fresh look at current circumstances. Chapters that concentrate on governance look at the distinction between "national," "public" and "private" institutions; others consider important topics such as internationalization, student recruitment, faculty mobility. More innovative topics include "Women of Color Leading in Japanese Higher Education." All provide copious references to other authorities, but rather than just toe the conventional line they include opinions and proposals that may be contentious or even revolutionary. The editor provides an overview of the subject and its treatment in an Introduction.